Utilization of wheat straw for fungal phytase production - Zohre Shahryari; Mohammad H. Fazaelipoor; Payam Setoodeh; Ramkumar B. Nair; Mohammad J. Taherzadeh; Younes Ghasemi (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Wheat straw is an agricultural waste which can be used as a cost effective animal feed. However, high hemicellulose and phytic acid content in wheat straw prevents it as a primary feed choice. Utilization of wheat straw in solid-state fermentation may result in wheat straw valorization and enzyme production. In this study, phytase production in solid-state fermentation of wheat straw using Aspergillus ficuum and valorization of wheat straw were evaluated. Methods A two-step experimental design procedure was employed for screening and optimization of influencing factors on phytase production. Effects of different nutritional and environmental factors were investigated by one factor at the time method (OFATM). To reach higher amounts of phytase, response surface methodology (RSM) was employed to optimize phytase production as a function of three of the most effective factors. Results Optimization of the significant parameters resulted in an increase in the phytase activity from 0.74 ± 0.12 to a maximum of 16.46 ± 0.56 Units per gram dry substrate (U gds−1). The high degree of the fungal phytase activity on wheat straw resulted in the decrease in phytic acid content by 57.4%, as compared to the untreated sample. Scanning electron microscopy (SEM) and FTIR structural analysis showed intensive fungal growth on wheat straw, and partial removal of hemicelluloses, lignin and phytic acid. Conclusion The study demonstrated the feasibility of wheat straw utilization in solid-state fermentation using Aspergillus ficuum toward the production of phytase and valorization of wheat straw as an animal feed.